Public Participation in Environmental Decision Making in Romania - Bogdana Neamtu; Dacian C. Dragos; Laura Capraru (Central European Public Administration Review)
This article researches the manner in which the participation pillar from the Aarhus Convention was transposed into Romanian legislation and how its provisions were applied to a highly controversial case. Thus, the paper will firstly address the general legal framework concerning participation in environmental matters as well as the challenges for the implementation of Aarhus Convention, followed by requirements for effective participation and NGOs involvement in the process. The main conclusion drawn is that public participation is generally seen only as a bureaucratic requirement that both authorities and the developer must meet before the project is adopted. In this context, the NGOs play a crucial role by acting as a real watchdog in identifying deficiencies in the application of the Convention. In order for enhancing implementation the authors emphasize the more proactive role that public authorities should have both with regard to the quality of environmental reports and with applying sanctions coupled with a stronger cooperation with the NGOs in the field.